The management of public expenditure in local administrative organizations in Southern-Thailand - Pichetwut, Nillaor (2014)
Public Expenditure Management (PEM) is an approach used to ensure effective management of resources in public sector organizations. A national reform has been made by the Thai government to improve management of public expenditure both at the central and local government. Since there are many problems in managing public expenditure at local government level, especially Tambon Administrative Organizations (TAOs), this study sets to investigate the effectiveness of PEM and the relationships between PEM's conditions and Aggregate Fiscal Discipline (AFD), Allocative Efficiency (AE) and Operational Efficiency (OE), which is tagged as PEM's elements. The researcher uses both quantitative and qualitative methods in this study. Questionnaire was designed to elicit information from two hundred and sixty-three (263) respondents, while in-depth interview was designed for nine (9) interviewees. Data used for the study was obtained from the Chief Administrators of the TAOs from nine (9) provinces in Southern Thailand. The findings of the study reveal that there exists medium strength level for AFD and AE, while OE has a high level. Also, it is found that a five (5) out of six (6) PEM's conditions are high. These five (5) requirements are political engagement, policy clarity, transparency, comprehensiveness, and accountability, while the strength of predictability is at a medium level. The relationship between conditions of PEM and PEM's element by using Pearson correlation method revealed that PEM's conditions are positively connected to PEM's elements. In addition, the study used multiple regressions to test the relationship between conditions of PEM and elements of PEM with respect to public resources. The findings disclose that the political engagement and accountability are related positively with the AFD. Similarly, the policy clarity is related positively with the AE and OE is related positively with the transparency. Lastly, the results show that the management of public expenditure in the local government in Thailand is facing problems in every element of PEM. There should be a proactive need to blend PEM's conditions with PEM's elements which will ultimately improve the capacity of PEM among administrators of TAOs. Finally, policy makers should endeavor to incorporate the effectiveness of PEM in the administrative organizations in order to bring efficiency into the public expenditure management of TAOs.